2008
DOI: 10.1016/j.humpath.2007.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein kinase C delta (PKCδ) expression in endometrial tumors

Abstract: Endometrial cancer is the most common gynecologic malignancy in the United States. However, its underlying molecular mechanisms are poorly understood; and few prognostic indicators have been identified. The protein kinase C (PKC) family has been shown to regulate pathways critical to malignant transformation; and in endometrial tumors, changes in PKC expression and activity have been linked to a more aggressive phenotype and poor prognosis. We have recently shown that PKC delta is a critical regulator of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…In addition to an important role in normal cells, these findings suggest a role for PRMT5 in skin cancer. PRMT5 levels are increased (29), and PKC␦ levels are decreased in cancer (59,60). Thus, the balance between these signaling inputs is likely to be important in disease development, and we anticipate that PRMT5 may serve to enhance skin cancer cell survival.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to an important role in normal cells, these findings suggest a role for PRMT5 in skin cancer. PRMT5 levels are increased (29), and PKC␦ levels are decreased in cancer (59,60). Thus, the balance between these signaling inputs is likely to be important in disease development, and we anticipate that PRMT5 may serve to enhance skin cancer cell survival.…”
Section: Discussionmentioning
confidence: 97%
“…PKC-␦ protein is also reduced in high grade endometrial and bladder cancers, but the mechanism of PKC␦ loss in these cancers has not been reported. [22][23][24] The PKC-␦ gene has been previously shown to be up-regulated by a variety of transcription factors. [25][26][27][28][29] The mechanism of reduced PKC-␦ gene expression in human SCCs is unknown, but is likely to involve Ras/ EGFR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It can induce both cell survival and apoptosis depending on cell types and its subcellular localization (2). For instance, treatment with anticancer agents resulted in a translocation of PKCy from cytoplasm into nucleus concomitant with induction of apoptosis (12,19,44). Our recent studies showed PKCy is involved in phosphorylation of p53 and potentiates p53-dependent apoptosis in response to DNA damage (17).…”
Section: Discussionmentioning
confidence: 99%